Enhanced Corrosion Resistance of AZ91 Alloy Produced by Semisolid Metal Processing. Issue 4 (29th January 2015) - Mingo, B.; Arrabal, R.; Mohedano, M.; Pardo, A.; Matykina, E.; Rivas, A.
Abstract : Rheocast AZ91 magnesium alloy was evaluated in terms of microstructure and corrosion resistance. Rheocasting leads to a globular microstructure of α-Mg spheres separated by an interconnected β-Mg17 Al12 (β-phase) network. Findings revealed that early stages of corrosion were located at the center of α-Mg globules and more importantly at α-Mg/β-phase interfaces due to galvanic coupling as predicted from surface potential maps. Electrochemical, hydrogen evolution and weight loss measurements demonstrated the superior corrosion resistance of the rheocast alloy. This was attributed to an improved barrier effect of the β-Mg17 Al12 phase and, possibly, to a smaller area fraction of Al-(Mn, Fe) inclusions. For long immersion times, only small attacked areas were observed which corresponded to randomly corroded α-Mg globules.